2002
DOI: 10.1002/jemt.10194
|View full text |Cite
|
Sign up to set email alerts
|

Carotid body and glomus cells distributed in the wall of the common carotid artery in the bird

Abstract: In the bird the carotid body is located between the distal (nodose) ganglion of the vagus nerve and the recurrent laryngeal nerve at the beginning of the common carotid artery, that is, the organ is located at the cervicothoracic border. The chicken carotid body receives numerous branches from the vagus and the recurrent laryngeal nerves. In addition, dense networks of the peptidergic nerve fibers immunoreactive for substance P, calcitonin gene-related peptide (CGRP), vasoactive intestinal peptide (VIP), galan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 60 publications
2
26
0
Order By: Relevance
“…Cells were quenched with staining medium (L15 medium containing 1 mg/ml BSA [Sigma A-3912], 10 mmol/l HEPES at pH 7.4, and 1% penicillin/streptomycin [BioWhittaker]). After centrifugation, the cells were resuspended in staining medium, filtered through a nylon screen (45 m; Sefar America) and stained with antibody against HNK-1 (CD57 membrane glycoprotein; BD Pharmingen), a marker that identifies tyrosine hydroxylase-positive glomus cells (26). The analysis and sorting of HNK-1 ϩ cells was performed by a MoFlo cytometer (DAKO Cytomation).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were quenched with staining medium (L15 medium containing 1 mg/ml BSA [Sigma A-3912], 10 mmol/l HEPES at pH 7.4, and 1% penicillin/streptomycin [BioWhittaker]). After centrifugation, the cells were resuspended in staining medium, filtered through a nylon screen (45 m; Sefar America) and stained with antibody against HNK-1 (CD57 membrane glycoprotein; BD Pharmingen), a marker that identifies tyrosine hydroxylase-positive glomus cells (26). The analysis and sorting of HNK-1 ϩ cells was performed by a MoFlo cytometer (DAKO Cytomation).…”
Section: Methodsmentioning
confidence: 99%
“…The physical association of chemoreceptive cells in the carotid artery of the tegu, however, differed from the general pattern seen in most other terrestrial taxa. The carotid chemoreceptors of amphibians and mammals are concentrated into highly vascularized structures (the carotid labyrinth and carotid body, respectively) (Gonzalez et al, 1994;Kameda, 2002;Kusakabe, 2002). In contrast, the chemoreceptive site in the tegu is best described as a modified artery with a lattice-like structure composed of cords of tissue crisscrossing the vessel lumen, within which the putative chemoreceptor cells are diffusely distributed.…”
Section: Evolution Of Carotid Chemoreceptionmentioning
confidence: 99%
“…For this study, we tested for cell markers of acetylcholine (ACh) and serotonin (5-HT) based upon their prevalence in the carotid chemoreceptor cells of other taxa. Catecholamine-and serotonincontaining cells are present in the chemoreceptive regions of fish, amphibians, birds and mammals (Banister et al, 1967;Kameda, 2002;Burleson et al, 2006;Prabhakar, 2006;Jonz and Nurse, 2012) whereas ACh is found in some fish and all mammals (Burleson and Milsom, 1995;Nurse, 2005). Although ACh is not found in the carotid chemoreceptors of all taxa, cholinergic putative chemoreceptor cells were recently found in chelonians (Reyes et al, 2015), leading us to include it in our study.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…There are previous studies on the morphologic structure and the topographic anatomy of the carotid body, thyroid gland, parathyroid gland and ultimobranchial gland of various avian species (4,9,13,16,17). The purpose of this study is to identify the localization of the thyroid gland, parathyroid gland and ultimobranchial gland spesific to reptile and avian species and in long-legged buzzards and to contribute to the anatomy literature.…”
Section: Introductionmentioning
confidence: 97%